Triphenylamine dyes having symmetric double D-TI-A configuration for dye-sensitized solar cells - Balanay, M. P.; Lee, S. H.; Kim, D. H. (Nazarbayev University, 2014)
The conformation of the dye on the semiconductor is an important factor for the improvement of charge injection and minimization of the back electron transfer process. In addition, the dye should be able to suppress aggregation by introducing bulky alkyl groups, addition of co-adsorbents, or designing a dye with a п-bridge between two chromophores forming a spiro-like configuration [1,2]. This study presents the synthesis of two compounds having double D-TT-A configurations namely, KS-11 and KS-13 and comparing their photovoltaic properties with the rod-like configuration, herein labelled as KS-10.
Keywords: photovoltaic; synthesis; configuration; chromophores; electrolyte; photophysical; electrochemical